Role of H2S Supplementation on Burn Wound Healing and Molecular Chaperones - Verma, Saurabh; Keshri, Gaurav K.; Sharma, Manish; Gupta, Asheesh (Defence Life Science Journal, 2021)
Treatment of non-healing burn injuries is a major challenge for the current scientific research. Hydrogen sulfide (H2S) is an endogenous gasotransmitter, which regulates redox homeostasis and cytoprotection during pathophysiological conditions. Similarly, heat shock proteins (HSPs) are molecular chaperones, which also confer cytoprotection during the wound repair process. Notably, the role of H2S as a regulator of HSPs during burn wound healing is still elusive. The present study investigated the effects of H2S supplementation on molecular chaperones during full-thickness, third-degree burn wound healing in the experimental rats. The animals were treated with sodium hydrosulphide (NaHS) as H2S donor (5 mg/kg body weight, intraperitoneal) daily for 10 days prior to burn-induction and continued till the fifth-day post-wounding. Histopathological analysis (Masson’s trichrome) revealed enhanced wound healing evident by increased collagen fiber deposition, cellular proliferation and re-epithelialisation in NaHS administered group as compared to the burn control. Furthermore, immunoblot analyses demonstrated significantly increased protein expression of molecular chaperons viz. HSP90, HSP70, HSP27, and GRP78 in H2S treated group as compared to control. Therefore, the present study signifies that H2S supplementation upregulates the protein expression levels of molecular chaperones, which could facilitate the cytoprotection during the tissue repair process and accelerates the burn wound healing.